Pedagogical mediation and creativity: new cognitive ecologies for the transformation of education (Revista Electrónica Calidad en la Educación Superior, 2018)
This essay has the intention to go through diverse co-constructed reflections, regarding creativity as an inherent process of the human being, that contributes to the generation of new forms to relate among ourselves, to assess processes, of looking and acting in the everyday nature, in such a way that it can contribute to the re-structuration of the cognitive ecologies so that they can attract again learning from the potentiality of the individual-species-society. Thus, the creative processes are considered that have re-blended up to the present the learning experiences, trying to decipher, from multiple perspectives (interrelated), the forms of re-configuring consciously their possibilities in new spaces, in multiple encounters, in renewed ways of sharing with Others, of being with Others (human beings).